Applicability of the Movement Assessment Battery for Children-Second Edition (MABC-2) for Japanese Children Aged 3–6 Years: A Preliminary Investigation Emphasizing Internal Consistency and Factorial Validity - Hirata, Shogo; Kita, Yosuke; Yasunaga, Masanori; Suzuki, Kota; Okumura, Yasuko; Okuzumi, Hideyuki; Hosobuchi, Tomio; Kokubun, Mitsuru; Inagaki, Masumi; Nakai, Akio (Frontiers in Psychology, 2018)
This study investigated the applicability of the Movement Assessment Battery for Children – Second Edition (MABC-2) for 3- to 6-year-old Japanese children, particularly addressing its internal consistency and factorial validity. The MABC-2 test set for 3- to 6-year-old children was administered to 252 children. Differences between Japanese children and those of the original normative sample (i.e. United Kingdom children) were investigated along with sex differences. The Japanese children aged 3–6 years were found to have higher Manual Dexterity and Balance component scores than children of the normative sample. Girls scored higher than boys on the Balance component. Results of several analyses showed good internal consistency of the MABC-2. Confirmatory factor analysis revealed that a theoretical three-component model of the MABC-2 was not fitted to Japanese children aged 3–6 years. Instead, a new three-component model was postulated and discussed. The new three-component model of the MABC-2, with Manual Dexterity, Static Balance and Ball Skills, and Dynamic Balance, has high factorial validity in Japanese children aged 3–6 years.